Photo-Energized MoS2/CNT Cathode for High-Performance Li–CO2 Batteries in a Wide-Temperature Range - Hu, Tingsong; Lian, Wenyi; Hu, Kang; Li, Qiuju; Cui, Xueliang; Yao, Tengyu; Shen, Laifa (Nano-Micro Letters, 2024)
Li–CO2 batteries are considered promising energy storage systems in extreme environments such as Mars; however, severe performance degradation will occur at a subzero temperature owning to the sluggish reaction kinetics. Herein, a photo-energized strategy adopting sustainable solar energy in wide working temperature range Li–CO2 battery was achieved with a binder-free MoS2/carbon nanotube (CNT) photo-electrode as cathode. The unique layered structure and excellent photoelectric properties of MoS2 facilitate the abundant generation and rapid transfer of photo-excited carriers, which accelerate the CO2 reduction and Li2CO3 decomposition upon illumination. The illuminated battery at room temperature exhibited high discharge voltage of 2.95 V and mitigated charge voltage of 3.27 V, attaining superior energy efficiency of 90.2% and excellent cycling stability of over 120 cycles. Even at an extremely low temperature of − 30 °C, the battery with same electrolyte can still deliver a small polarization of 0.45 V by the photoelectric and photothermal synergistic mechanism of MoS2/CNT cathode. This work demonstrates the promising potential of the photo-energized wide working temperature range Li–CO2 battery in addressing the obstacle of charge overpotential and energy efficiency. Highlights: 1 The unique layered structure and excellent photoelectric properties of MoS2 facilitate the abundant generation and rapid transfer of photo-excited carriers, which accelerate the CO2 reduction and Li2CO3 decomposition upon illumination. 2 MoS2-based photo-energized Li–CO2 battery displays ultra-low charge voltage of 3.27 V, high energy efficiency of 90.2%, superior cycling stability after 120 cycles and high rate capability. 3 The low-temperature Li–CO2 battery achieves an ultra-low charge voltage of 3.4 V at –30 °C with a round-trip efficiency of 86.6%.